Highly Efficient Synthesis of Hindered 3-Azoindoles via Metal-Free C–H Functionalization of Indoles - Jacob, Nicolas; Guillemard, Lucas; Wencel-Delord, Joanna (Synthesis, 2020)
Although 3-azoindoles have recently emerged as an appealing family of photoswitch molecules, the synthesis of such compounds has been poorly covered in the literature. Herein a high-yielding and operationally simple protocol is reported allowing the synthesis of 3-azoindoles, featuring important steric hindrance around the azo motif. Remarkably, this C–H coupling is characterized by excellent atom economy and occurs under metal-free conditions, at room temperature, and within few minutes, delivering the expected products in excellent yields (quantitatively in most of the cases). Accordingly, a library of new molecules, with potential applications as photochromic compounds, is prepared.
Keywords: azoindole; C–H functionalization of indoles; azoswitches; diazenylation